The Effect of Motivational Interviewing on Motivation, Knowledge, And Self-Care in Colorectal Cancer Patients with a Stoma: A Case Study - Yayu Nidaul Fithriyyah; Yati Afiyanti; Gayatri Dewi (NERS Jurnal Keperawatan, 2026)
Colorectal cancer with a stoma impacts the patient's physical, psychological, social, and spiritual well-being. It requires long-term adaptation in self-care, often leading to a decrease in motivation. This study aims to assess the effect of Motivational Interviewing (MI) interventions on enhancing motivation, knowledge, and self-care in colorectal cancer patients with a stoma. The case study involved 10 patients selected through purposive sampling in Dharmais Cancer Hospital. The participants received two structured MI sessions (15-60 minutes). Participants were provided with a health booklet and a daily activity plan book. Data analysis used descriptive univariate statistics and the Framework Method. The average motivation score increased from 49.3 to 56.7 after the first session and to 61.2 after the second session. The highest score was in the domain of value/usefulness, while the lowest was in the domain of interest/enjoyment. Self-care knowledge improved from "Sufficient" (55%) to "Good" (75%). Self-care practices also improved, with stoma care increasing (10% to 70%), nutrition (100%), and exercise (20% to 80%). Intimate relations are only the "rarely" category (20%). Motivational Interviewing (MI) enhances motivation, knowledge, and self-care scores in colorectal cancer patients with a stoma. However, intimate relations remain limited. The study recommends the routine application of MI in nursing practice. Future studies should include larger sample sizes and focus on patients with limited family support and more diverse characteristics.